The Use of Educandy Media on Learning English in the Covid 19 Pandemic Era - Anggita Dwi Saputri; Anita Rachmawati Putri; Gina Aufa Yusuf Sabilla; Triwulan Triwulan; Susilawati Susilawati (Candradimuka: Journal of Education, 2023)
The Corona Virus (Covid 19) which began to hit this country in early 2020 not only had an impact on health, but also in terms of the economy and even education. Students are required to take online learning. Changes in the system of learning activities from face to face to online are considered boring for students. The process of learning English which is carried out online is considered less effective and makes student learning outcomes decrease so that interesting media are needed to be able to motivate and improve student learning outcomes. For this reason, researchers apply Educandy as an alternative to game-based learning that is not boring. Educandy is a website-based application that has the slogan "making learning sweeter" which can be used as a learning evaluation. The use of educandy with a more attractive, colorful and easy-to-apply appearance makes the learning experience more impressive. The purpose of this study was to find out how the use and effectiveness of Educandy media in learning English to become a motivating and fun educational game for students. The approach used by researchers in this study is to use a quantitative approach. The source of research data is the students of Ash Shoheh 2 Citeureup Vocational High School, totaling 20 people. Data collection techniques are using questionnaires and test questions to measure student learning outcomes. As for the results obtained, researchers can show the effectiveness of Educandy media on learning English during online learning in the covid 19 pandemic era.